Benefits of Giving Egg White Extract and Moringa Leaves to Improve The Nutritional and Immune Status of TB Patients. A Scoping Review - Novi Kusrini; Herin Mawarti; Yuly Peristiowati; Achmad Zakaria (Universitas STRADA Indonesia, 2024)
TB is still a major global health concern, especially in developing nations like Indonesia, which has the third-highest rate of TB cases globally. Mycobacterium tuberculosis infection has a negative effect on the health of the patient as well as causing low serum albumin levels, poor nutritional status, and other blood abnormalities, all of which worsen the general health of those who are infected. Nutritional supplements, particularly egg white and milk containing moringa extract, have the potential to improve nutritional status and speed up TB patients' recuperation. The protein-rich egg white may raise albumin levels, while the nutrient-dense moringa boosts immunity. Furthermore, encouraging treatment adherence and halting the disease's spread require nutritional measures and family support.